Место и время социологии - Костенко, Н.; Макеев, С. (Социология: теория, методы, маркетинг, 2008)
It is well known that periodical statements of crisis of social sciences proved constantly to be new turns and vistas revealing each time untapped resources of sociology. The essence of modern claims sociologists agree with is in evident weakening of refe rentiality — sociology is losing the contact with “society”, with that which constituted it both as a science and as a special intellectual practice. This fact seems to prejudice the very ability to be a “modern science about modern society”. The authors believe that the paradox of the current situation lies in the parallel existence both of uncertainty about the key point of the discipline and concern about adequacy of methods, as well as in quite convincing experience of combining tradition and innovation in the works of N.Luhmann, P.Sztompka, L.Thеvenot and L.Boltanski, J.Urry, that engenders the phenomenon of “new old sociology”. The article deals with metamorphoses of tempo rality the social disciplines are concerned with when describing local and extremely wide spaces of human coexistence.